ANTESEDEN DAN KONSEKUENSI DARI CUSTOMER SATISFACTION PADA PRODUK HEMAT ENERGI - Zidane, Nevada Ali; Faisal, Aekram (JURSIMA, 2025)
This study aims to examine the influence of Function Value, Price Value, Emotional Value, Social Value, and Environmental Value on Consumer Satisfaction, as well as its impact on Willingness to Pay a Premium, Repurchase Intention, Positive Word of Mouth Intention, and Customer Lifetime Value in the context of energy-saving products. A quantitative approach was applied using a survey method involving 262 consumers of energy-saving products in Jakarta. The research design involved hypothesis testing, and data were collected cross-sectionally through an online questionnaire. Data analysis was conducted using validity and reliability tests, along with Structural Equation Modeling (SEM). The results indicate that most dimensions of Consumer Perceived Value significantly affect Consumer Satisfaction. Furthermore, Consumer Satisfaction has a significant effect on consumer loyalty outcomes, including Willingness to Pay a Premium, Repurchase Intention, Positive Word of Mouth Intention, and Customer Lifetime Value. These findings are expected to serve as a reference for industry players in developing marketing strategies that prioritize consumer satisfaction to foster long-term loyalty.